CLASSIFICATION OF FACTORS AFFECTING THE LIVING STANDARD OF THE RURAL POPULATION - Ochilov, Akram Odilovich; Alimova, Munisa Yulchievna (THE INNOVATION ECONOMY, 2025)
The article describes the theoretical aspects of raising the standard of living of the rural population, the factors influencing them, the mechanisms, priorities and main results of the reforms implemented today to improve the standard of living of the rural population. In addition, this article reflects ways to improve the effectiveness of the measures implemented in the agricultural sector.